Study of Literature Researching Factors Affecting Problem Financing in Indonesia's Sharia Banking During 2017-2021 - Mai Simahatie; Lakharis Inuzula (PT. Radja Intercontinental Publishing, 2022)
This study aims to make a literature review of research related to the factors that affect the financing of non-performing Islamic banking in Indonesia. The importance of this research is because non-performing financing of Islamic banks continues to increase and can be dangerous. This study uses a qualitative descriptive method and collects articles using the publish or perish application with restrictions from 2017 to 2021. The results: the factors that affect non-performing financing in Islamic banking occur due to external factors and internal factors. from internal companies such as procedural errors in providing financing, fraud, analysis errors, managerial abilities, lack of supervision and monitoring,) and from debtors such as character, sick debtors, education, family (internal macro factors of the company). Furthermore, External Factors can be caused by macroeconomics, such as market conditions, government regulations, politics, natural disasters. (Company external macro factors). Meanwhile, macroeconomic factors that influence non-performing financing include inflation, currency exchange rates, GDP, BI Rate and CAR, FDR and so on. , Inflation, Inflation Control Range , BI rate , BOPO CAR, GDP, Rupiah exchange rate ROA, CPI, GDP, LTV, PLS CPI, GDP, CAR, FDR, PLS inflation, exchange rate, profit sharing, and per capita income rate, Wadiah Certificate Bank Indonesia,